The communicative power of blood sacrifices : a predominantly South African perspective with special reference to the Epistle to the Hebrews - Van der Watt, J.G. (Jan Gabriel), 1952- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2008.